(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Thе article examines the issues of increasing the reliability of power supply through the use of modern means of protection in the power supply system, which is an important part of the electric power industry. Recommendations have been developed to create comfort for working personnel by using modern microprocessor protective equipment instead of electromechanical relay protection devices in the current state of power networks, to reduce the gabarit of the constructions, to increase reliability in ensuring electrical safety and continuity of power supply